1997
DOI: 10.1021/ie950704v
|View full text |Cite
|
Sign up to set email alerts
|

FCC Riser Unit Operated in the Heat-Transfer Mode:  Kinetic Modeling

Abstract: A pilot-plant unit, namely, Multicrackex, for the catalytic cracking of hydrocarbons with the riser and regenerator units under direct heat exchange conditions was developed in the course of the present study. A two-levels pseudofactorial experimental program was designed using the synthetic gas oil SF-135 (CANMET) and a commercial equilibrium catalyst (Akzo Octaboost). Using the experimental temperature profile inside the riser, the reaction rate constants and activation energies were evaluated for the four l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 4 publications
1
10
0
Order By: Relevance
“…The main advantage of this model is its ability to predict coke production. This four lump model was used for the development of correlations and carry out different parametric studies on various aspects of FCC modeling [5][6][7][8][9]. Five lump kinetic models developed by Ancheyta et al [10] and Bollas et al [11] included 7 and 9 rate constants respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The main advantage of this model is its ability to predict coke production. This four lump model was used for the development of correlations and carry out different parametric studies on various aspects of FCC modeling [5][6][7][8][9]. Five lump kinetic models developed by Ancheyta et al [10] and Bollas et al [11] included 7 and 9 rate constants respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Three or more lumps are usually considered (Weekman and Nace, 1970, Nace et al, 1971, Jacob et al, 1976, Derouin et al 1997, Ali and Rohani, 1997, Blasetti and De Lasa,, 1997, Arandes et al 2000. Therefore, it is common practice to use a "lumping" technique to model the reaction kinetics.…”
Section: Introductionmentioning
confidence: 99%
“…The inclusion of the above discussed constants into the mathematical model implied the modification of Equations (9) and (11). Then, the two equations were rewritten, respectively, as follows:…”
Section: Inverse Methodology Of Parameter Estimationmentioning
confidence: 99%
“…It was also shown that the catalyst deactivation function is dependent on the feedstock type. On the other hand, simple kinetic models, with a small number of lumps, 5,11,12 require fewer kinetic constants to be determined and are simple to solve numerically.…”
Section: Introductionmentioning
confidence: 99%